Ethno-Religious Conflicts in Nigeria: A Threat to The Quest for National Integration - Idongesit David Udom; Ugo Chuks Okolie (The Indonesian Journal of International Clinical Legal Education, 2022)
Nigeria as an independent nation cannot discuss her history without recounting her sad experience of one conflict or the other. Notable among these conflicts are those of communal, political and ethno-religious conflicts which often result in destructive violence. Out of all these, ethno-religious conflicts appear to have more implications to national development, security and integration in Nigeria. This paper is an empirical survey of existing literature through secondary investigations. The paper posits that colonialism and its capitalist ideological underpinnings and the transplanting of the same character traits to Nigeria bourgeoisie elements largely accounts for the ethnic divide pervading the Nigerian system. Over and above this argument is the malicious ethnic structures initially created by colonialism which has brought about continuous and contending ethnic strife in the Nigerian state to date. The position of this paper is also that the new trend of criminality and the gory tradition of terrorism and security lapses ravaging the country in most states of the North during the Jonathan’s administration and most states of the North-Central during the Buhari’s administration is akin to ethnic and sectional sentiments as well as ethnic bias. In view of this, the paper therefore attempts to draw explanations on why ethno-religious conflicts have become a permanent feature of Nigeria and its implications to national integration. This paper further takes a peep into the effects of ethno-religious conflicts on economic development in Nigeria. The paper sums up with policy recommendations and conclusion for peaceful co-existence in the 21st century.